Novel SMAD3 Mutation in a Patient with Hypoplastic Left Heart Syndrome with Significant Aortic Aneurysm - Kristi K. Fitzgerald; Abdul Majeed Bhat; Katrina Conard; James Hyland; Christian Pizarro (Case Reports in Genetics)
Aneurysms-osteoarthritis syndrome (AOS) caused by haploinsufficiency of SMAD3 is a recently described cause of syndromic familial thoracic aortic aneurysm and dissection (TAAD). We identified a novel SMAD3 mutation in a patient with hypoplastic left heart syndrome (HLHS) who developed progressive aortic aneurysm requiring surgical replacement of the neoaortic root, ascending aorta, and proximal aortic arch. Family screening for the mutation revealed that his father, who has vascular and skeletal features of AOS, and his brother, who is asymptomatic, also have the pathogenic mutation. This is the first case report of a SMAD3 mutation in a patient with hypoplastic left heart syndrome. This case highlights the importance of genetic testing for known causes of aneurysm in patients with congenital heart disease who develop aneurysmal disease as it may significantly impact the management of those patients and their family members.